Implementasi Bantuan Hukum Bagi Masyarakat Tidak Mampu di Posbakum Pengadilan Agama Sukabumi - Henny Suryaningsih; Asti Sri Mulyanti; Temmy Fitriah Alfiany (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research was conducted because of the background of the use of the Legal Aid Post of the Sukabumi Religious Court which was deemed not fully effective so that the author was interested in examining the services provided by the Legal Aid Post of the Sukabumi Religious Court to the Disadvantaged Community. This research was also conducted to determine the implementation of the service provision of the Legal Aid Post of the Sukabumi Religious Court. The author uses an empirical juridical method that is guided by the Law and examines directly in the field by conducting interviews. The existence of posbakum among the public is still unfamiliar and there are still many people who do not know about posbakum and use the services of advocates who require the public to pay. This results in a lack of information for the wider community about the role of the Legal Aid Post which functions as legal aid for the poor.